Dampak penggunaan gadget terhadap kepribadian anak sekolah dasar: studi kasus pada siswa ‘X’ - Hidayat, Fahrul; Hernisawati, Hernisawati; Maba, Aprezo Pardodi (Jurnal Humaniora dan Ilmu Pendidikan, 2021)
Purpose: This study aimed to determine the extent of the influence of gadgets on elementary school children, especially in the aspect of personality, as well as how parents' efforts in providing supervision and direction for their children. Research methodology: This type of research is qualitative with the case study method. The instruments used were observation, interviews, and documentation. Meanwhile, for data analysis, researchers used descriptive-analytic techniques. The data analyzed is then tested for validity using the credibility, transferability, dependability, and confirmability tests. Results: The results of this study indicate that there is an effect of gadgets on children's personalities, including temperament, indifference, a fast-developing mindset without appropriate stages, love to share, and be creative. Limitations: This research is far from perfect; the author realizes that there are limitations in the research process, one of which is that the subject and object of research are only taken within the scope of the family. Contribution: This research is expected to be useful in the world of education, especially educators and the family environment as a reference in implementing digital parenting for their children. Keywords: Gadgets, Personality, Children, Parents